2022
DOI: 10.1159/000524059
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance in the Brain: Evidence Supporting a Role for Inflammation, Reactive Microglia, and the Impact of Biological Sex

Abstract: Increased intake of highly processed, energy-dense foods combined with a sedentary lifestyle are helping fuel the current overweight and obesity crisis, which is more prevalent in women than in men. Although peripheral organs such as adipose tissue contribute to the physiological development of obesity, emerging work aims to understand the role of the central nervous system to whole body energy homeostasis and development of weight gain and obesity. The present review discusses the impact of insulin, insulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 150 publications
(186 reference statements)
0
1
0
Order By: Relevance
“…These inflammatory cascades further inhibit IRS-1, ultimately leading to insulin resistance. Among these inflammatory pathways, inflammation induced by microglial activation has been established as a critical component in inducing insulin resistance ( Doust et al, 2022 ), and studies have demonstrated that inhibiting microglial activation can restore insulin resistance-related cognitive decline ( Chunchai et al, 2018 ). Moreover, the presence or absence of the components of the inflammatory cascade can improve insulin resistance.…”
Section: Potential Mechanisms Of Exercise In Improving Insulin Resist...mentioning
confidence: 99%
“…These inflammatory cascades further inhibit IRS-1, ultimately leading to insulin resistance. Among these inflammatory pathways, inflammation induced by microglial activation has been established as a critical component in inducing insulin resistance ( Doust et al, 2022 ), and studies have demonstrated that inhibiting microglial activation can restore insulin resistance-related cognitive decline ( Chunchai et al, 2018 ). Moreover, the presence or absence of the components of the inflammatory cascade can improve insulin resistance.…”
Section: Potential Mechanisms Of Exercise In Improving Insulin Resist...mentioning
confidence: 99%